2014
DOI: 10.1177/0898264314538661
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Biological Markers of Health

Abstract: Objective The study documents whether socioeconomic status (SES) differentials in biological risk are more widely observed and larger in the United States than Taiwan. Method Data come from the Social Environment and Biomarkers of Aging Study in Taiwan and the Midlife in the United States study. We use regression analyses to test whether four summary measures of biological risk are significantly related to categorical measures of education, income, and subjective social status among four country-sex specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Health disparities exist on the basis of many aspects of identity, including racial/ethnic background, 1–3 SES, 4,5 gender, 6,7 age, 8,9 as well as indicators of healthy versus nonhealthy body weight. 10,11 Recently, it has been suggested that health-care stereotype threat (HCST) might be one of the overlooked pathways whereby minority and stigmatized identities contribute to health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Health disparities exist on the basis of many aspects of identity, including racial/ethnic background, 1–3 SES, 4,5 gender, 6,7 age, 8,9 as well as indicators of healthy versus nonhealthy body weight. 10,11 Recently, it has been suggested that health-care stereotype threat (HCST) might be one of the overlooked pathways whereby minority and stigmatized identities contribute to health disparities.…”
Section: Introductionmentioning
confidence: 99%